Answer:
x = -4 , y = -6
Step-by-step explanation using elimination:
Solve the following system:
{10 x - 7 y = 2 | (equation 1)
{6 x - 7 y = 18 | (equation 2)
Subtract 3/5 × (equation 1) from equation 2:
{10 x - 7 y = 2 | (equation 1)
{0 x - (14 y)/5 = 84/5 | (equation 2)
Multiply equation 2 by 5/14:
{10 x - 7 y = 2 | (equation 1)
{0 x - y = 6 | (equation 2)
Multiply equation 2 by -1:
{10 x - 7 y = 2 | (equation 1)
{0 x+y = -6 | (equation 2)
Add 7 × (equation 2) to equation 1:
{10 x+0 y = -40 | (equation 1)
{0 x+y = -6 | (equation 2)
Divide equation 1 by 10:
{x+0 y = -4 | (equation 1)
{0 x+y = -6 | (equation 2)
Collect results:
Answer: {x = -4 , y = -6